Improving electrocatalytic activities of FeCo2O4@FeCo2S4@PPy electrodes by surface/interface regulation. (June 2020) - Zhao, Depeng; Dai, Meizhen; Zhao, Yue; Liu, Hengqi; Liu, Ying; Wu, Xiang
Abstract: Constructing bi-functional electrocatalysts with multi-active sites is significant to enhance the catalytic performances. However, it is still a large challenge to obtain high efficient catalysts for full water electrolysis. Herein, we design novel sandwich-like FeCo2 O4 @FeCo2 S4 @PPy catalysts through a facile preparation strategy. The as-fabricated samples present an excellent electrocatalytic performance with an overpotential of 98.2 mV for HER at −10 mA cm −2, 280 mV for OER and a cell voltage of 1.63 V at 50 mA cm −2 . The outstanding performances can be contributed to in-situ electrochemical activation and synergistic effects of electrode materials. It benefits to surface/interface modulation forming active Co and Fe oxyhydroxides in electrochemical reaction process. Graphical abstract: In this work, a newly designed sandwich FeCo2O4@FeCo2S4@PPy catalyst is constructed through a simple method. The as-fabricated samples present an excellent electrocatalytic performance for OER and HER, and a small cell voltage of 1.63 V at 50 mA cm-2. Image 1 Highlights: FeCo2 O4 @FeCo2 S4 @PPy sandwich structures are prepared through a simple preparation route. PPy layer can accelerate surface reconstruction and electron transfer. The in-situ electrochemical pre-oxidation effectively increase the electroactive sites and form metal hydroxides. The as-fabricated products present superior electrocatalytic performance with a small overpotential and long stability.